2015
DOI: 10.1590/1678-7174
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de níveis de glicina+serina em dietas de frangos de corte com reduzido teor de proteína bruta

Abstract: RESUMOO experimento foi conduzido em delineamento inteiramente ao acaso para avaliar os efeitos de diferentes níveis de glicina+serina (gli+ser) total em dietas de baixa proteína bruta (PB) Atualmente existe grande pressão, não apenas para reduzir os custos de produção, mas também para reduzir desperdícios e eliminação de elementos poluentes, dentre os quais está o nitrogênio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…By analyzing the performance of quails fed diets T 1‐1 versus T 1‐2 , it was observed that the protein reduction and the supplementation of limiting essential amino acids (T 1‐2 ) did not significantly alter the feed intake of quails in relation to the control diet (T 1‐1 ), in which there was no reduction of crude protein. These data corroborate with Applegate et al (), Darsi et al (), Hernandez et al (), Vasconcellos et al () and Vasconcellos et al (), who did not verify a reduction in feed intake in broilers and/or laying hens by reducing the dietary crude protein level and supplementing with only the limiting amino acids.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…By analyzing the performance of quails fed diets T 1‐1 versus T 1‐2 , it was observed that the protein reduction and the supplementation of limiting essential amino acids (T 1‐2 ) did not significantly alter the feed intake of quails in relation to the control diet (T 1‐1 ), in which there was no reduction of crude protein. These data corroborate with Applegate et al (), Darsi et al (), Hernandez et al (), Vasconcellos et al () and Vasconcellos et al (), who did not verify a reduction in feed intake in broilers and/or laying hens by reducing the dietary crude protein level and supplementing with only the limiting amino acids.…”
Section: Resultssupporting
confidence: 89%
“…Darsi et al (), Hernandez et al (), Vasconcellos et al () and Vasconcellos et al () did not observe a difference for the variables mentioned above in broilers fed a control diet in relation to a diet with protein reduction and supplemented only with limiting essential amino acids.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations